Counseling for Facilitating Changes in families: A Model for Intervention - Villarreal-Montoya, Cecilia (2020)
Family education requires epistemological clarity to provide a basis for praxis. Working collectively with family groups is a significant learning resource to enhance their strengths. The article presents the systematization of a model for intervention in family counseling, consolidated in the university extension project titled “Orientando Familias” (POF, acronym in Spanish) by the Universidad Nacional de Costa Rica. Its purpose is to strengthen facilitation skills with systemic theoretical and methodological bases in professionals of diverse areas so that they can plan preventive actions aimed at improving the quality of relationships in families. Reports, chronicles, videos, photographs, and oral evaluations of each of the sessions conducted were used as inputs. The project was implemented in schools, the National Children’s Hospital, the Ministry of Justice and Peace, and in the CEN-CINAIs of the Metropolitan Area of San José, Limón, Sarapiquí, Guanacaste, Pérez Zeledón, and Puntarenas. Fifty-nine people were trained, twenty-six education plans were created, and 345 people and their families were benefited. The facilitators were able to reconceptualize the families from the relational coexistence and the construction of bonds, the reunion with the family itself, greater knowledge about family dynamics, generation and developing of own projects, and staging a more relational intervention to facilitate change. The systemic methodological intervention allowed the professionals to provide families with learning experiences and personal significance promoting opportunities to work in the transformation of the family system and favor better forms of social coexistence.